Contemporary issues in human resource development - Abdul Hamid, Zabeda; Osman-Gani, Aahad M. (Pearson, 2011)
Organisations are increasingly recognising the significant impacts of investing in human capital for continuous development of relevant competencies in maintaining their competitive advantage. Superior talent is being recognised as the prime source of sustainable competitive advantage in high performance organisations. Along with the need for a talented workforce, the knowledge base of the organisation has to be managed effectively and efficiently and this brings a need for better knowledge management in organisations. This leads to overall better human resource development (HRD) within the company. This chapter looks at the talent management practices that focuses on development, retention and utilisation of talent. Furthermore, knowledge management initiatives of acquisition, sharing and retention of knowledge are also discussed. Sustainable development with emphasis on environmental awareness education and corporate social responsibility will also be touched upon. Finally, this chapter discusses contemporary HRD issues relating to the globalisation and cross-cultural HRD relevant to developing global managers and creating a culturally sensitive workforce for effective performance in an increasingly globalised business environment.